Combined treatment for gastric cancer: Immunological approach - Zhandossov, Olzhas; Kaussova, Galina; Koten, Avraam (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Gastric cancer is one of the most common oncological diseases. It can develop in any part of the stomach and spread to other organs, especially the esophagus, lungs, and liver. The aim of our study was to investigate the effectiveness of our proposed therapy. Materials and Methods: Our research promises more effective neoadjuvant therapy, including immunotherapy and multi-agent chemotherapy. Of the 62 patients involved in our study, 32 underwent neoadjuvant chemotherapy in combination with surgery, whereas the rest underwent neoadjuvant chemoimmunotherapy with surgery. Results: Investigation of T-cell-mediated and humoral immunity in patients with gastric cancer over the course of treatment found a reduction of the main indices of cell-mediated and humoral immunity in the patients who underwent standard therapy, which greatly caused a decline of antitumor, anti-infective, and antitoxic protection of the patients’ organisms. Conclusion: This study can contribute to the development of new therapies for gastric cancer as well as other types of cancer. Cite this article as: Zhandossov O, Kaussova G, Koten A. Combined treatment for gastric cancer: Immunological approach. Turk J Gastroenterol 2018; 29: 151-6.